Effects of Slow Deep Breathing on Acute Clinical Pain in Adults: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Amira E. Joseph MD; Rajat N. Moman MD, MA; Ross A. Barman DO; Donald J. Kleppel MD; Nathan D. Eberhart; Danielle J. Gerberi MLIS; M. Hassan Murad MD; W. Michael Hooten MD (SAGE Publishing, 2022)
Slow deep breathing (SDB) may help patients with acute pain. The primary aim of this systematic review and meta-analysis is to investigate the effects of SDB on acute pain. Secondary aims include investigating the effects of SDB on acute pain-related physical and emotional functioning. An a priori protocol was registered and a database search was conducted by a reference librarian. Randomized controlled trials (RCT) were eligible for inclusion and exclusion criteria included studies of SDB for non-pain indications and studies that applied SDB as a component of an encompassing intervention. The risk or bias was assessed using the Cochrane Collaboration's revised tool for assessing risk of bias in randomized trials. Meta-analysis was conducted using the random effects model. A total of 11 968 studies were screened and seven RCTs met inclusion criteria; five were judged to have low risk of bias. Meta-analysis of post-intervention pain scores demonstrated that SDB was associated with significantly lower pain scores compared with a control group, but with high levels of heterogeneity. Subgroup analyzes demonstrated that trials of burn pain were associated with a larger reduction in pain which partially explains the heterogeneity. Very low certainty evidence suggests that SDB may reduce acute pain intensity. Further research is needed to identify patients who are candidates for SDB and determine the best approach to deliver this therapy.